2000
DOI: 10.1063/1.373683
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of field emission display phosphors

Abstract: Degradation of ZnS and Y2O2S cathodoluminescent (CL) phosphors has been studied at 1–4 keV using Auger electron spectroscopy simultaneous with CL. The data are consistent with an electron stimulated surface chemical reaction (ESSCR) which led to destruction of ZnS and formation of a surface nonluminescent ZnO layer as well as injection of oxygen point defects into the near-surface region. In the case of Y2O2S:Eu, the electron beam stimulated removal of S and formation of Y2O3:Eu in the presence of 1×10−6 Torr … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 13 publications
3
36
0
Order By: Relevance
“…To generate the values of t, Eqn (5) can be rearranged so that t D erf 1 2P 1 6 which returns a value of t 2 [ 4,4] for any given random number P between 0 and 1.…”
Section: Distributing Electrons Over a Surface According To A Gaussiamentioning
confidence: 99%
“…To generate the values of t, Eqn (5) can be rearranged so that t D erf 1 2P 1 6 which returns a value of t 2 [ 4,4] for any given random number P between 0 and 1.…”
Section: Distributing Electrons Over a Surface According To A Gaussiamentioning
confidence: 99%
“…Their data support a model called electron-stimulated surface chemical reaction (ESSCR). 4 According to this model, the reactive gas molecules adsorb onto the surface of the ZnS. The molecules are dissociated by the electron beam from molecular species to form reactive atomic species, which results in the formation of a ZnO surface layer and volatile SO 2 , 5 with the consequent loss of cathodoluminescence (CL) intensity.…”
Section: Introductionmentioning
confidence: 99%
“…It was demonstrated that when these phosphors were irradiated with the beam of electrons for a long period of time they lose their CL intensity and this occured simultaneously with desorption of oxygen (O) from the phosphor surfaces. In the process, an oxygen deficient non-luminescent layer was formed on the surface whose formation could be explained by an electron stimulated surface chemical reaction (ESSCR) model proposed by Holloway and co-workers (Holloway et al, 1996(Holloway et al, , 2000. The desorption of atomic species was explained by Knotek-Fiebelman electron stimulated desorption (ESD) proposed by Knotek and Feibelman (Knotek and Feibelman, 1978).…”
Section: Introductionmentioning
confidence: 99%
“…In this case, a non-luminescent oxide layer, which is known to reduce the CL intensity of the CRT/FED phosphors, may form on the surface. For examples, it was demonstrated that when zinc sulfide (ZnS) based phosphors were exposed to a prolonged irradiation by energetic beam of electrons, the ZnS host dissociated into reactive ionic Zn 2+ and S 2-species, which in turn combined with ambient vacuum gases such as O 2 and H 2 O to form non-luminescent ZnO or ZnSO 4 layers or H 2 S gas (Swart el al., 1998;Itoh et al, 1989) as explained by the ESSCR model (Holloway et al, 1996(Holloway et al, , 2000. In the case of oxide based systems, the electron beam induced dissociation of atomic species is followed by desorption of oxygen from the surface.…”
Section: Cathodoluminescence Intensity Degradationmentioning
confidence: 99%